Poetics of profession in literature and history: Life in the archive (2017) by Lila Caimari and The writing book (2021) by Gabriela Bejerman - María Guillermina Feudal (Estudios de Teoría Literaria)
The poet Gabriela Bejerman and the historian Lila Caimari coin innovative textualities to attend the beginnings of a writing and research Project, and accompany the processes of those who begin the practice. They conceive the temporality of the beginnings as an open and discontinuous time, irreducible to the form of the final work. To argue the need to reconvert production time into an active aesthetic process, they refer to their own experiences and introduce fictional scenes in which the variety of emerging positions is observed during the preparatory phases. The article analyzes the principles of their respective poetics of the profession, a hypothesis that allows a comparison between the foundations of their arts and their communication strategies. The different disciplinary backgrounds of the authors – literature, history – reveal a shared need to unravel the intensities of practice usually repressed in the procedural demands of specialized discursive communities. Due to the way of listening to the preparatory time in its aesthetic and epistemological quality, their texts can be considered contemporary works of art.